1999
DOI: 10.1159/000026612
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of Aluminum in Mice: Influence of Restraint Stress

Abstract: The influence of restraint stress on potential aluminum (Al)-induced behavioral changes was assessed in CD-1 mice. Three groups of adult mice were given 0, 300 and 600 mg Al/kg body weight per day in drinking water for 2 weeks. One-half of the animals in each group were concurrently subjected to restraint stress during 1 h per day throughout the study. After cessation of treatment, open-field activity, active avoidance learning, and motor resistance and coordination of the animals were evaluated. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The results of this study showed that SI treatment improved the long memory performance of chronically Al exposed mice. Concerning the correlation of Al with learning and memory ability, previous studies have shown that Al may involve the formation of neurofi brillary tangles and cognitive defi cits in Alzheimer's disease (Alleva et al, 1998;Colomina et al, 1999;Golub et al, 1995;Neill et al, 1996;Pratico et al, 2002). A large increase of Al content in experimental animals due to Al exposure was observed in the hippocampus, which is the site of memory and learning (Julka and Gill, 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of this study showed that SI treatment improved the long memory performance of chronically Al exposed mice. Concerning the correlation of Al with learning and memory ability, previous studies have shown that Al may involve the formation of neurofi brillary tangles and cognitive defi cits in Alzheimer's disease (Alleva et al, 1998;Colomina et al, 1999;Golub et al, 1995;Neill et al, 1996;Pratico et al, 2002). A large increase of Al content in experimental animals due to Al exposure was observed in the hippocampus, which is the site of memory and learning (Julka and Gill, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Extensive studies have shown a potential link between chronic aluminum (Al) exposure and cognitive defi cits (Akila et al, 1999;Alleva et al, 1998;Colomina et al, 1999;Nayak and Chatterjee, 2001;van Rensburg et al, 2001). Aluminum is considered a potential etiological factor in Alzheimer's disease because Al might induce characteristic brain neurofi brillary of the disease (ElRahman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, the neurobehavioural studies model mainly acute high (e.g. Colomina et al 1999;Yen-Koo 1992) but not long-term and moderate Al exposure representing a model of occupational life time loads.…”
Section: Models Of Al Neurotoxicitymentioning
confidence: 99%
“…Colomina et al 1999), a necessary but not sufficient prerequisite for central neurobehavioural effects. A relatively direct admission of Al from the air to the brain is also possible over olfactory paths, whereas the significance of the uptake is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 includes a number of studies by Colomina and collaborators in which restraint during organogenesis in mice was not effective in producing fetal effects (Colomina et al, 1995,1997,1998,1999a,1999b,2001; Albina et al, 2002; Torrente et al, 2002). These studies were conducted to examine the possible interaction between stress and toxicant administration, rather than the effects of stress alone.…”
Section: Endpoints Affected By Restraint: Effects Produced Organogenesismentioning
confidence: 99%